Evaluation on the performance of a signalized intersections - Nor Ain Nadia, Mohamad Zaid (2017)
Intersection is where the vehicle from other direction meet. If the number of vehicle increase, this will cause a worst traffic flow when need to change the lane or direction during driving. Nowadays, traffic flow is the common problem occur not only in the urban but also in rural area due to the increases of vehicle. Therefore, this study is intended to evaluate the performance of a signalized intersection during weekdays and weekend in terms of level of service (LOS) at the intersection. In order to achieve this, the T- signalized intersection that located at Batu 10, Jalan Gambang have been chosen as study area. The data collection will be recorded in several days during peak hour morning and evening on weekdays and weekend by manual count. Determination of traffic volume and geometric characteristic will figure out the delays and level of service (LOS). Based on the analyses, the cycle length and insufficient of lane cause the condition of this study area become worst. In order to improve the future operating level of service (LOS) the improvement that have been proposed are reduce the cycle length and make some change in the geometrical design such as added the number of lanes for the critical lanes. The improvement of the level of the service for the whole intersection will improve the performance of the intersection.